Dynamic behaviors of a molten carbonate fuel cell under a sudden shut-down scenario: The effects on temperature gradients - Law, M.; Lee, Vincent; Tay, C. (2015)
© 2015 Elsevier Ltd. All rights reserved. A three-dimensional (3-D), dynamic model of a molten carbonate fuel cell (MCFC) is developed in the current work. The model takes into account the heat and mass transfers of various reacting gas species. Yuh and Selman's model is implemented to solve the voltage-current relationship. In addition, water-gas shift (WGS) reaction is also included in the model. The simulation result is validated with published experimental data. The model is used to study the effects of steady and pulsating flows on the temperature gradients of MCFC electrodes in a shut-down event. Co-flow and counter-flow of MCFC are included in this study. The results show that higher thermal conductivity and smaller gas temperature difference before and after shut down event ensure better structural integrity of the fuel cell. In addition, under the simulated condition, the counter-flow operating condition is better for MCFC due to its overall lower temperature and also temperature gradients. In the case of the pulsating flow, the change of electrode temperature gradient is greater in co-flow MCFC compared to that of counter-flow MCFC. The sinusoidal profile of an electrode temperature gradient is more visible when both anode and cathode gas channels are subject to pulsation. A steady gas flow ensures a lower maximum temperature gradient in an electrode. Nevertheless, the simulation result also shows that under certain pulsating flow conditions, the cathode electrode will have a lower average temperature magnitude compared to that of steady-flow.